Vacuoles, E1 enzyme, X-linked, autoinflammatory, somatic (VEXAS) syndrome: A comprehensive review of cases across different ethnicities - Zhu, Yixiang Yves-Jean; Beck, David Benjamin; Dieudonné, Yannick; Georgin-Lavialle, Sophie (European journal of internal medicine, 2025)
•VEXAS is more described in Caucasians but has a broad global distribution.•The disease should be investigated regardless of patients’ origin or ethnicity.•The disparity highlights challenges in accessing genetic testing in some countries. Vacuoles, E1 enzyme, X-linked, autoinflammatory, somatic (VEXAS) is an autoinflammatory disease associated with somatic mutations in the UBA1 gene. Although the disease has been described in many different countries, no studies have investigated the origin of patients to determine if the disease is universal across ancestries. The aim of this study is to investigate the distribution of VEXAS syndrome across continents and ethnicities. A literature review of all reported cases of VEXAS syndrome was conducted between October 2020 and April 2025 using the term 'VEXAS' with the all-field filter in the Pubmed and Web of Science databases. Epidemiological and clinical data were collected for included patients. If the country of origin was not described, it was assumed to be the same as the country of clinical evaluation. A subgroup analysis was performed for patients whose country of origin or ethnicity was documented by the authors. 674 cases of VEXAS syndrome were collected, with patients described from four continents and 32 countries. Considering the subgroup of patients with documented country of origin, 451 patients were from four continents and 19 countries. Of these, ethnicity was recorded for 372 patients with the presence of Caucasian, Central or East Asian, South Asian, Middle Eastern, Central American and South American ethnicities. The results support a broad global distribution of the disease and highlight the importance of investigating the disease regardless of the patient's origin and ethnicity in cases of compatible symptoms. [Display omitted]